A new species of Microcurgus Haupt, 1950 (Hymenoptera, Pompilidae) from Oman - Al-Jahdhami, Ali; Schmid-Egger, Christian (Zootaxa, 2020)
Microcurgus samedensis is described from Northern Oman by a single female. It represents the first record of the genus from the Arabian Peninsula. A key to females from the Palearctic region is given.